Dynamic communication performance of a TESH network under the nonuniform traffic patterns - Rahman, M.M. Hafizur; Inoguchi, Yasushi; Sato, Yukinori; Miura, Yasuyuki; Horiguchi, Susumu (2008)
Interconnection networks play a crucial role in the performance of massively parallel computers. Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computer systems. The Tori-connected mESH (TESH) Network is a 2D-torus network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher level networks. In this paper, we present a deadlock-free routing algorithm for the TESH network using 2 virtual channels - 2 being the minimum number for dimension-order routing - and evaluate the network's dynamic communication performance under various nonuniform traffic patterns, using the proposed routing algorithm. We evaluate the dynamic communication performance of TESH, mesh, and torus networks by computer simulation. It is shown that the dynamic communication performance of the TESH network is better than that of the mesh and torus networks.